ANALYSIS SPECIFIC ACTIVITY OF XYLANASE ENZYME PRODUCED BY THE CONSORTIUM OF THERMOPHILIC BACTERIA FROM SAPAN SUNGAI ARO HOT SPRING - Yeriska, Feby; Mulia; Irdawati; Advinda, Linda; Hilda Putri, Dwi (Jurnal Serambi Biologi, 2023)
Thermophilic bacteria are bacteria that are able to survive in high temperatures ranging from 45 – 80oC so that they have the potential to produce enzymes that are stable against heat. Thermophilic bacteria can be found in various places in nature that have potential hot springs. One of the potentials of thermophilic bacteria in producing enzymes is the xylanase enzyme. Xylanase is able to hydrolyze xylan (hemicellulose) into xylo-olisaccharides and xylose. In the industrial world, xylanase enzymes are used as paper whiteners, increase the volume of bread, as juice purification, and are used in the manufacture of detergents. This research is a type of descriptive research that aims to determine the specific activity of the xylanase enzyme and the levels of xylanase protein produced by thermophilic bacteria SSA (Sapan Sungai Aro) with bacterial isolates SSA3, SSA4, SSA5, SSA6, SSA7, SSA8, SSA13, SSA14 and SSA15. The results showed that the bacterial isolates SSA3, SSA4, SSA5; isolates SSA6, SSA7, and SSA8; and SSA13, SSA14 and SSA15 respectively had specific activity of the xylanase enzyme with an average value of 0.1614 Unit/mg; 0.1638 Unit/mg and 0.1473 Unit/mg. The final measurement results showed that the highest specific activity of the xylanase enzyme was in the consortium of thermophilic bacteria isolates SSA6, SSA7, and SSA8 with an average of 0.1638 Unit/mg.